2007
DOI: 10.1080/13880200701214748
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Flavonol Glycosides fromEuphorbia hirta.

Abstract: Bioassay-guided fractionation of the MeOH extracts of Euphorbia hirta Linn (Euphorbiaceae) aerial parts led to the isolation of flavonol glycosides afzelin (1), quercitrin (2), and myricitrin (3), whose structures were established by MS and NMR analysis. Compounds 1-3 showed proliferation inhibition of Plasmodium falciparum, with IC 50 values of 1.1, 4.1, 5.4 mg=mL, repectively. On the other hand, they exhibited little cytotoxic property against human epidermoid carcinoma KB 3-1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 33 publications
2
45
1
3
Order By: Relevance
“…Alguns constituintes ativos da E. hirta têm sido detectados, destacando-se a presença de flavonoides tais como a quercetina (Hallet & Parks, 1951;Liu et al, 2007), leucocianidina e xantoramnina (Newall et al, 2002), afazelina e miricitrina (Liu et al, 2007), o que condiz com o resultado encontrado na prospecção fitoquímica realizada neste trabalho. Estudo de Bhagwat et al (2008) revelou a presença de esteroides, alcaloides, carboidratos, proteínas e compostos fenólicos (flavonoides, taninos e saponinas).…”
Section: Aunclassified
See 2 more Smart Citations
“…Alguns constituintes ativos da E. hirta têm sido detectados, destacando-se a presença de flavonoides tais como a quercetina (Hallet & Parks, 1951;Liu et al, 2007), leucocianidina e xantoramnina (Newall et al, 2002), afazelina e miricitrina (Liu et al, 2007), o que condiz com o resultado encontrado na prospecção fitoquímica realizada neste trabalho. Estudo de Bhagwat et al (2008) revelou a presença de esteroides, alcaloides, carboidratos, proteínas e compostos fenólicos (flavonoides, taninos e saponinas).…”
Section: Aunclassified
“…(mobot, 2012), é conhecida popularmente como erva-andorinha, erva-de santa luzia, folha-de-leite ou eufórbia. Na composição encontram-se alcanos, triterpenos, fitosterois, taninos, polifenois e flavonoides (Liu et al, 2007;Kumar, 2010). Esta planta tem sido utilizada em caso de distúrbios respiratórios, tais como asma, bronquite, espasmo laríngeo (Corrêa, 1984;Newall et al, 2002), e no tratamento de amebíase intestinal (Newall et al, 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…They were previously reported in C. dioscoridis 20 , E. hirta 21 Acute toxicity (median lethal dose; LD 50 …”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the LC 50 of ethyl acetate and acetone extract of Euphorbia hirta were 71.15 and 92.15 ug/ml respectively [101].On the other hand, flavonol glycosides (afzelin, quercitrin and myricitrin) isolated from the methanolic extract of the aerial parts of Euphorbia hirta, exhibited little cytotoxic property against human epidermoid carcinoma KB 3-1 cells [102].The leaf extract of Euphorbia hirta also appeared toxic based on the viability of the cells by in vitro analysis on the lymphocytes from normal blood cells [72].…”
Section: Anticancer Effectmentioning
confidence: 99%